Low-intensity pulsed ultrasound enhances antibiotic release of gentamicin-loaded, self-setting calcium phosphate cement. Issue 7 (July 2018) - Shi, Mingmin; Chen, Lei; Wang, Yangxin; Yan, Shigui
Objective: This study aimed to investigate the effect of low-intensity pulsed ultrasound on antibiotic release from gentamicin-loaded, self-setting calcium phosphate cement. Methods: A gentamicin-loaded calcium phosphate cement cylinder was eluted in stimulated body fluid. Low-intensity pulsed ultrasound (46.5 kHz, 200 mW/cm 2 ) was used to produce a sinusoidal wave in the experimental group. Non-gentamicin calcium phosphate cement was used in the control group. Results: The transient concentration and cumulatively released percentage of gentamicin in the ultrasound group were higher than those in control group at every time point. The duration of gentamicin concentrations over the level of the minimum inhibitory concentration was significantly prolonged in the ultrasound group compared with the control group. Antibacterial efﬁcacy of gentamicin in the ultrasound group was significantly better than that in the control group with the same concentration of gentamicin. Conclusion: Low-intensity pulsed ultrasound enhances antibiotic release, providing sustained antibiotic release at high concentrations. This increases the antibacterial effect of gentamicin.